Sugarcane Characteristics Preferred by the Farmers to Plant in the Philippines: Impact to Production - Oñal, Paulino Miguel M.; Oñal, Jr., Paulino A (Future Science / FSH-PH Publications, 2026)
Sugarcane (Saccharum officinarum, L.) is a perennial plant in the Poaceae family. It is considered an important crop because it has the capacity to produce sucrose, accounting for up to 50% of the dry weight of a mature stalk. In the Philippines, the sugarcane industry is one of the major dollar income industries. The study aims to determine the different sugarcane characteristics preferred by the farmers to plant and their relation to the volume of production in the Philippines. The descriptive-correlation method was employed in the study. The instrument used was the validated survey questionnaire used by the group of Oñal in their study in 2021. The 320 sugarcane farmers were randomly identified at the seven locations in the Visayas area of the Philippines. Analysis of variance (ANOVA) implied that there’s a significant difference in the production of sugarcane among the different locations in the Philippines. On sugarcane characteristics, the color of the stalks, stalk growth morphology, and the number of millable stalks at harvest implied a significant difference in production. The stalk color and number of millable stalks at harvest were strongly correlated with the volume of production. The studyrevealed that in the characterization of sugarcane varieties in the Philippines, the stalk color and number of millable stalks should be given an impetus before releasing the varieties to farmers. The results of the study will enhance the government's average national target of production to 75 tons/ha and sustain the Philippine sugar industry.